Non-invasive assessment of motor unit anatomy in jaw-elevator muscles - CASTROFLORIO, T.; FARINA, D.; BOTTIN, A.; DEBERNARDI, C.; BRACCO, P.; MERLETTI, R.; ANASTASI, G.; BRAMANTI, P. (Journal of oral rehabilitation, 2005)
summary The estimation of fibre length in jaw‐elevator muscles is important for modelling studies and clinical applications. The objective of this study was to identify, from multi‐channel surface EMG recordings, the main innervation zone(s) of the superficial masseter and anterior temporalis muscles, and to estimate the fibre length of these muscles. Surface EMG signals were collected from 13 subjects with a 16‐electrode linear array. The innervation zones of the masseter and anterior temporalis were identified and their variability intra‐ and inter‐subject outlined. More than one main innervation zone location was identified in the masseter of all subjects and in the temporalis anterior of 12 subjects. Average estimated fibre lengths, for the right (left) side, were (mean ± SD) 27·3 ± 2·4 mm (27·0 ± 1·7 mm) and 25·9 ± 2·3 mm (26·6 ± 1·6 mm), for the superficial masseter and temporalis anterior muscle, respectively. The range of innervation zone locations was up to approximately 50% of the fibre length, both within and between subjects. Fibre length estimates well matched with published data on cadavers. It was concluded that multi‐channel surface EMG provides important and reliable information on the anatomy of single motor units in jaw‐elevator muscles.